PENYELESAIAN KLAIM PRULINK (PRUDENTIAL UNIT LINK) DI PT. PRUDENTIAL LIFE ASSURANCE PEKANBARU - Amelia, Sri Ayu; Ismi, Hayatul; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
insurance has two types of insurance namely health insurance and life insurance. Health insurance is one of the insurance products that have several categories. The main categories of health insurance are income disability insurance, assuming traditional medical costs. Furthermore life insurance is a socioeconomic tool, which is the way of a group of people to be able to work together to reduce the burden due to the premature death of the members of the group. In insured life insurance is caused by death (death). Such deaths result in the loss of income of a person or a particular family. Risks that may arise in life insurance mainly lies in the